1985
DOI: 10.1002/ijc.1985.36.3.321
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Beta‐carotene Intervention Trial With Inuits Using Smokeless Tobacco

Abstract: The frequency of exfoliated cells with micronuclei (MNC) was used to estimate the genotoxic effect of smokeless tobacco (snuff) on the oral mucosa and to follow the response to the administration of beta-carotene (180 mg/week, given twice weekly in 6 capsules of 30 mg each). The pilot trial was carried out with Inuits in Gjoa Haven, Northwest Territories, Canada. Their traditional diet, which is rich in caribou and seal meat and liver but low in vegetables and fruits, leads to "normal" serum levels of retinol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The approximately 30% reduction in micronuclei after P-carotene treatment is in accordance with the effect of Pcarotene reported in buccal mucosa of betel nut chewers (Stich et al, 1984a) and tobacco chewers (Stich et al, 1985(Stich et al, , 1988. Our findings extend these observations to cigarette smoke-induced tracheobronchial micronuclei, which may reflect lung cancer risk (Stich & Rosin, 1984b;Lippman et al, 1990a,b).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The approximately 30% reduction in micronuclei after P-carotene treatment is in accordance with the effect of Pcarotene reported in buccal mucosa of betel nut chewers (Stich et al, 1984a) and tobacco chewers (Stich et al, 1985(Stich et al, , 1988. Our findings extend these observations to cigarette smoke-induced tracheobronchial micronuclei, which may reflect lung cancer risk (Stich & Rosin, 1984b;Lippman et al, 1990a,b).…”
Section: Discussionsupporting
confidence: 91%
“…P-Carotene has been shown to reduce micronucleated buccal mucosal cells in tobacco chewers (Stich et al, 1984a(Stich et al, , 1985(Stich et al, , 1988 and may thus reduce risk for oral cancer. These trials, however, did not measure plasma levels of P-carotene and retinol.…”
mentioning
confidence: 99%
“…19 Previous studies on retinoids as primary chemopreventives (to reverse oral leukoplakias) showed that the protective effect persisted while the drug was being taken but that leukoplakias recurred when it was stopped. [11][12][13][14][15] How long the effect lasted after drug withdrawal was not assessed. We found that the protective effect of 4-HPR against recurrences and new leukoplakias lasted for 7 months after drug withdrawal, though CIs were dependent on the size of the sample, both because of the original sample size and the fact that it reduced with follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Some have found that these substances may have such an action by promoting the disappearance of oral leukoplakias. [11][12][13][14][15] In other studies, retinoids had an adjuvant chemopreventive effect by reducing the incidence of new head-and-neck carcinomas. [16][17][18][19] However, no studies have been conducted on the use of retinoids for adjuvant chemoprevention of new head-and-neck carcinomas after removal of oral leukoplakia.…”
mentioning
confidence: 95%
“…One of the markers used to define chromosomal aberrations is the staining for micronuclei in exfoliated buccal mucosal cells (Stich et al, 1985). Micronuclei have also been used to evaluate the reversal of leukoplakia and the effectiveness of retinoids, carotenoids, and vitamin E (Stich et al, 1988;Brenner et al, 1993 for oral cancer development will be noted in this review only as they have been covered in detail in other recent articles (Andrewetal., 1994;Field etal., 1995;Jin etal., 1995).…”
mentioning
confidence: 99%